Evaluation of two empirical wind erosion models in arid and semi-arid regions of China and the USA. (May 2017) - Pi, Huawei; Sharratt, Brenton; Feng, Gary; Lei, Jiaqiang
Abstract: Wind erosion models are important tools for assessing soil erodibility and identifying management practices to control erosion. The Agricultural Policy/Environmental eXtender (APEX) model and Revised Wind Erosion Equation (RWEQ) were tested using data collected from the Tarim Basin of China and Columbia Plateau of the United States of America. Adequate performance in simulating soil loss was achieved using the original APEX model and RWEQ in respectively a cotton field and desert-oasis ecotone in the Tarim Basin and winter wheat - summer fallow (WW-SF) field in the Columbia Plateau. We calibrated the APEX model and RWEQ to improve performance because both models have many empirical parameters. After calibration, both models adequately simulated soil loss from all land use types except the RWEQ from the red date orchard in the Tarim Basin. Inadequate performance of the calibrated RWEQ in the red date orchard was likely due to underestimating maximum mass transport. Highlights: Performance of the APEX model and RWEQ was tested in China and USA. The wind erosion models were compared under different land cover types. Both models, when uncalibrated, inadequately simulated soil loss. Calibration improved the performance of both models.